SEJARAH MINANGKABO (Minangkabau ?) DALAM NASKAH, BUKU LANGKA DAN PETA KUNO - Noranda, Alfa (Jurnal Ceteris Paribus, 2023)
In West Sumatra in general, people know that Minangkabo's traditional form of government is Nagari. In historical chronology, the social structure of pre-colonial society is rarely revealed. This is because the composition of pre-colonial society and government is not widely sourced and written down in modern historical narratives. Therefore, not many people know how the social life before the colonial sat and changed the shape of Minangkabo's social structure. By using manuscripts and literacy sources from rare books using the methodology of Historiography, Historiarchaeology, Manuscript Transliteration and Ancient Map Analysis in this paper, the author tries to reveal things that are rarely the concern of many people. The findings of the information reveal other aspects and are different from what is generally known by people in the present. The Minangkabo people and the existing Traditional Government had a great influence when the trade office and representative Gurbernur in Batavia, the Government of the Republic of Batavia in Eastern Europe, was just pioneering its position which eventually controlled the entire archipelago which is currently known as Indonesia.